The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19159569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sinus Floor Augmentation with Platelet-Rich Fibrin Versus Allogeneic Bone Graft on Stability of One-Stage Dental Implants: A Split-Mouth Randomized Clinical Trial

Abstract: Rehabilitation of an edentulous posterior maxilla with dental implants is challenging, and sinus floor augmentation could be considered as an important surgical procedure for bone augmentation in this region before implant placement. Platelet-rich fibrin (PRF) is a new-generation platelet concentrate with simplified processing: its application in sinus floor augmentation has been widely investigated in literature. However, the biological properties and actual efficacy of this product remain controversial. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A split-mouth randomized control trial showed that there was no statistically significant difference between trans-crestal sinus floor elevation using PRF plugs in test side and blood clot in control side as a sole filling material. [14] Otherwise, Enhanced average height and bucco-palatal width at the height of the old and new sinus floor were seen in the PRF group, as well as increased bone gain in the mesial, buccal, and palatal areas more than control.…”
Section: Prf In Sinus Floor Elevationmentioning
confidence: 81%
“…A split-mouth randomized control trial showed that there was no statistically significant difference between trans-crestal sinus floor elevation using PRF plugs in test side and blood clot in control side as a sole filling material. [14] Otherwise, Enhanced average height and bucco-palatal width at the height of the old and new sinus floor were seen in the PRF group, as well as increased bone gain in the mesial, buccal, and palatal areas more than control.…”
Section: Prf In Sinus Floor Elevationmentioning
confidence: 81%
“…According to the findings, both groups experienced a significant increase in the mean ISQ over time. However, the PRF group showed a more significant increase, leading to better implant stability than the other group (Karagah et al, 2022). Platelet-rich derivatives can be used as the sole bone replacement material for maxillary sinus floor elevation.…”
Section: Prf Alone For Maxillary Sinus Floor Elevationmentioning
confidence: 92%
“…Kungvarnchaikul [22] No data available according to inclusion criteria Karagah [23] No data available according to inclusion criteria Grasso [24] No comparison with allograft bone…”
Section: Author Reasonmentioning
confidence: 99%